An Eye on Vision: Five Questions About Vision Screening and Eye Health. (May 2018) - Nottingham Chaplin, P. Kay; Baldonado, Kira; Bradford, Geoffrey E.; Cotter, Susan; Moore, Bruce
Current evidence-based and best-practice vision screening and eye health approaches, tools, and procedures are the result of revised national guidelines in the past 3 years and advances in research during the past 18 years. In providing answers to the five questions in this article, the National Center for Children's Vision and Eye Health at Prevent Blindness used published, peer-reviewed research; vision screening and eye health national guidelines; and consensus-based best practices from eye care professionals and public health experts. The answers may differ from your state or district vision screening guidelines and mandates. This is the second installment of the "An Eye on Vision" frequently asked questions section that will appear in future editions of NASN School Nurse. To review the first installment, see the March 2018 edition of NASN School Nurse. The authors encourage vision screeners to submit their vision screening and eye health questions to the email address that appears at the end of this article.